High Performance Liquid Chromatographic and Ultra Violet Spectroscopic Determination of Etoricoxib in Pharmaceutical Formulations - K. SHAKYA, ASHOK; A. KHALAF, NOOMAN (Asian Journal of Chemistry, 2010)
A simple, reliable and reproducible high performance liquid chromatographic (HPLC) and UV spectroscopic methods (UV method) were developed for the analysis of etoricoxib formulation. The HPLC analysis was performed using BDS-Hypersil C-8 (150 × 4.6 mm, 5 μm, Thermo electron corporation, USA) column. The mobile phase used was water : acetonitrile : methanol (50 : 25 : 25, v/v/v) at a flow rate of 1.25 mL/min with ultraviolet detection at 284 nm at 20 ± 1ºC. UV spectroscopic analysis was performed at 284 nm. Extraction of etoricoxib from tablet was carried out using methanol. Linearity was observed in the concentration range from 5-50 μg/mL using HPLC. For UV spectroscopic analysis the linearity range was 5-35 μg/mL (at 284nm). The results, obtained by the two methods in pharmaceutical preparation were compared. There were no significant differences between the mean values and the precision. These validated methods are suitable for the determination of etoricoxib in pharmaceutical tablet formulations.